Marine protected areas and spatial fetishism: A viewpoint on destructive fishing in coastal Tanzania. (August 2018) - Raycraft, Justin
Abstract: This paper focuses on destructive fishing practices in coastal Tanzania. I argue that the dominant conservation narrative that increased capacity and 'political will' for enforcement of marine protected areas (MPAs) reflects a form of spatial fetishization, in that it overemphasizes the influence of space over social behaviour. I contend that Tanzanian MPAs offer bandage solutions to underlying structural problems that are contingent upon the inconsistent availability of social and financial resources for monitoring activities. I suggest that a paradigm shift is necessary, involving the de-territorialization of marine conservation discourse in Tanzania, and a movement towards addressing the underlying social, political and economic conditions that influence marine resource use.